STRATEGI MENCEGAH MUNCULNYA EKSES NEGATIF PASKA PEMBENTUKAN KOMPONEN CADANGAN DI INDONESIA - Nanto Nurhuda; Joni Widjayanto; Lukman Yudho Prakoso (Jurnal Inovasi Penelitian, 2021)
Article 27 paragraph (3) of the UUD 1945 that: "every citizen has the right and obligation to participate in efforts to defend the state". One of the efforts to defend the state is through the Reserve Component Forces (Komcad) formation program. The Komcad formation program is outlined in Law Number 23 of 2019 concerning Management of National Resources for Defense. The law states that the role of the community in efforts to defend the state through the reserve component is carried out voluntarily. This is different from the compulsory military program implemented in several countries such as South Korea, America, Singapore, Australia, and others. The recruitment of Komcad is voluntary and can be followed by all Indonesian citizens with an age limit of 18 to 35 years. Until now, the plan to form Komcad is still under discussion between ministries to determine the best scheme for implementing recruitment, education, and its use. However, the program for the formation of the Komcad received a lot of responses from the public, both pro and contra. There are many questions about this program, especially the issue of urgency, the education pattern used, and the most important one is the question regarding the status of the Komcad during mobilization and demobilization.